The relationship between painful diabetic peripheral neuropathy and functional status of older people in Kuantan, Pahang - Makhtar, Aniawanis; Syed Elias, Sharifah Munirah; Azizi, Athirah (Elsevier España, 2021)
This study aimed to determine the relationship between painful diabetic peripheral neuropathy and functional status among older people in Kuantan, Pahang. A cross-sectional study was performed by using an interviewer-administered questionnaire among 300 participants recruited from selective Primary Health Centres and endocrine clinics, Hospital Tengku Ampuan Afzan in Kuantan, Pahang. The data were analyzed by using SPSS version 22. The findings indicated that most participants reported neuropathic pain experience. The severity of pain was found to be significantly related to patients who had been diagnosed over 10 years ago, Indians patients and those who were treating their diabetes with insulin alone. No significant relationship was found between pain severity and functional status. The severity of pain and the associated factors suggest the need for a multidisciplinary approach to provide effective treatment to patients with painful diabetic peripheral neuropathy.